2013
DOI: 10.14366/usg.13015
|View full text |Cite
|
Sign up to set email alerts
|

Imaging features of complex sclerosing lesions of the breast

Abstract: Purpose:The purpose of this study was to evaluate the imaging features of complex sclerosing lesions of the breast and to assess the rate of upgrade to breast cancer.Methods:From March 2008 to May 2012, seven lesions were confirmed as complex sclerosing lesions by ultrasonography-guided core needle biopsy. Final results by either surgical excision or follow-up imaging studies were reviewed to assess the rate of upgrade to breast cancer. Two radiologists retrospectively analyzed the imaging findings according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…As in all ultrasound studies, the quality of the imaging is operator dependent. Myong et al 11 discovered that among their patients found to have CSL on mammography, on US all the lesions were categorized by Breast Imaging Reporting and Data System (BI-RADS) in category 4 or 5, but only 28.6% went on to upgrade to DCIS and invasive ductal carcinoma. Magnetic resonance imaging has higher sensitivity for breast cancer detection, compared to both mammography and ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…As in all ultrasound studies, the quality of the imaging is operator dependent. Myong et al 11 discovered that among their patients found to have CSL on mammography, on US all the lesions were categorized by Breast Imaging Reporting and Data System (BI-RADS) in category 4 or 5, but only 28.6% went on to upgrade to DCIS and invasive ductal carcinoma. Magnetic resonance imaging has higher sensitivity for breast cancer detection, compared to both mammography and ultrasound.…”
Section: Discussionmentioning
confidence: 99%